OGLE-2015-BLG-1670Lb: A Cold Neptune beyond the Snow Line in the Provisional WFIRST Microlensing Survey Field - Ranc, Clément; Bennett, David P.; Hirao, Yuki; Udalski, Andrzej; Han, Cheongho; Bond, Ian A.; Yee, Jennifer C.; Albrow, Michael D.; Chung, Sun-Ju; Gould, Andrew; Hwang, Kyu-Ha; Jung, Youn-Kil; et al. (The Astronomical journal, 2019)
We present the analysis of the microlensing event OGLE-2015-BLG-1670, detected in a high-extinction field very close to the Galactic plane. Due to the dust extinction along the line of sight, this event was too faint to be detected before it reached the peak of magnification. The microlensing light-curve models indicate a high-magnification event with a maximum of Amax 200, very sensitive to planetary deviations. An anomaly in the light curve has been densely observed by the microlensing surveys MOA, KMTNet, and OGLE. From the light-curve modeling, we find a planetary anomaly characterized by a planet-to-host mass ratio, q = 1.00 − 0.16 + 0.18 × 10 − 4 , at the peak recently identified in the mass-ratio function of microlensing planets. Thus, this event is interesting to include in future statistical studies about planet demography. We have explored the possible degeneracies and find two competing planetary models resulting from the s ↔ 1 s degeneracy. However, because the projected separation is very close to s = 1, the physical implications for the planet for the two solutions are quite similar, except for the value of s. By combining the light-curve parameters with a Galactic model, we have estimated the planet mass M2 = 17.9 − 8.8 + 9.6 M ⊕ and the lens distance D L = 6.7 − 1.3 + 1.0 kpc , corresponding to a Neptune-mass planet close to the Galactic bulge. Such events with a low absolute latitude ( b 1 1 ) are subject to both high extinction and more uncertain source distances, two factors that may affect the mass measurements in the provisional Wide Field Infrared Survey Telescope fields. More events are needed to investigate the potential trade-off between the higher lensing rate and the difficulty in measuring masses in these low-latitude fields.